alpha1 and alpha2 domains of Aotus MHC Class I and Catarrhini MHC Class Ia share similar characteristics. (2013)
Functional and structural analyses of major histocompatibility complex (MHC) class I molecules of the Aotus genus are necessary to validate it as a solid animal model for biomedical research. We thus isolated, cloned and sequenced exons 2 and 3 from three Aotus species (A. nancymaae, A. nigriceps and A. vociferans). We found 24 sequences, which divided into two different groups (Ao-g1 and Ao-g2). A further sequence was identified as a processed pseudogene (Aona-PS2). Both sequence evolution and variability analyses showed that Ao-g1 and Ao-g2 display similar characteristics to Catarrhini’s classical loci, such as positive selection pressure at the peptide binding region (PBR) high variability and a trans-specific evolution pattern.